Clinical & laboratory profiles and treatment outcome of Kawasaki disease in children: Experience from a tertiary care hospital - Shareen Khan; Md Abid Hossain Mollah; Abdul Baki; Nabila Tabassum; Nasreen Islam; Amrita Lal Halder; Tasnima Ahmed; Nurun Nahar Fatema; Jebun Nahar; Fauzia Mohsin; Mohammod Jobayer Chisti (PLoS ONE, 2025)
Background A total of 40 cases of Kawasaki Disease (KD), diagnosed & categorized on the basis of criteria set by the American Heart Association were studied. We sought to evaluate their clinical and laboratory analysis along with their treatment. Methods After inclusion, they underwent thorough clinical and laboratory analysis and were treated with intravenous immunoglobulin and aspirin. Their clinical & laboratory findings and treatment outcome were analyzed further using Epi info and at a probability of (p value) < 0.05, was considered statistically significant. Results The mean age of the cases was 4.1 ± 2.9 years and boys outnumber the girls (57% vs. 43%). Most (65%) of the cases were incomplete KD compared to 35% as complete KD. The mean duration of fever was 11.7 ± 5.53 days. The frequency of the different classic clinical findings of KD were- cracking of lips & redness of oral cavity (72%), polymorphous skin rash (50%), conjunctival injection (45%), changes in the distal extremities (38%), cervical lymphadenitis (30%) and erythema on BCG scar (7.5%). High C-Reactive protein (CRP > 10 mg/dl), thrombocytosis, anaemia and leukocytosis were 85%, 45%, 43%, 38% respectively. Echocardiography showed coronary artery abnormalities (CAA) dilatation and aneurysm in 82.5% and 12.5% cases respectively which came down to 68% and 10% after receiving treatment with IVIg and Aspirin. Conclusion & Recommendation Diagnosis of KD is essentially clinical and criteria-based and 95% were complicated with CAA. Timely intervention with IVIG was mostly effective. Therefore, high index of suspicion of a long-continued febrile child is recommended to reach the diagnosis and to initiate timely intervention so as to potentially prevent CAA.